2016
DOI: 10.1016/j.bbi.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Immature monocytes recruited to the ischemic mouse brain differentiate into macrophages with features of alternative activation

Abstract: Acute stroke induces a local inflammatory reaction causing leukocyte infiltration. Circulating monocytes are recruited to the ischemic brain and become tissue macrophages morphologically indistinguishable from reactive microglia. However, monocytes are a heterogeneous population of cells with different functions. Herein, we investigated the infiltration and fate of the monocyte subsets in a mouse model of focal brain ischemia by permanent occlusion of the distal portion of the middle cerebral artery. We separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 47 publications
8
110
1
Order By: Relevance
“…Our data are consistent with the observations by Gliem et al [8] of reduced accumulation of differentiated macrophages (identified as Ly6c lo F4/80 hi ) in CCR2 −/− mice 6 days after ischemia. Thus, CCR2 + Ly6C hi Mo/MΦ could be precursors for CX3CR1 + Ly6C lo Mo/MΦ from which they develop through environmental cues provided by the ischemic brain tissue, as has been recently suggested [19]. The signals and their target receptors responsible for this phenotypic shift remain to be determined.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our data are consistent with the observations by Gliem et al [8] of reduced accumulation of differentiated macrophages (identified as Ly6c lo F4/80 hi ) in CCR2 −/− mice 6 days after ischemia. Thus, CCR2 + Ly6C hi Mo/MΦ could be precursors for CX3CR1 + Ly6C lo Mo/MΦ from which they develop through environmental cues provided by the ischemic brain tissue, as has been recently suggested [19]. The signals and their target receptors responsible for this phenotypic shift remain to be determined.…”
Section: Discussionmentioning
confidence: 87%
“…Low rates of Mo/MΦ proliferation have also been reported in a mouse model of permanent cerebral ischemia [19]. Considering these low proliferation rates, it is more likely that the increased numbers of brain Mo/MΦ are the result of continuous recruitment of hematogenous monocytes than from cell proliferation in situ.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, 10 % to 20 % of monocytes that express low CD43 are classified as a proinflammatory subset and the remaining monocytes that expresses higher levels of CD43 are classified as an anti-inflammatory subset [79]. Recently, CD43 has also been used to distinguish monocyte subsets in mice [80]. Classically activated proinflammatory monocytes express CCR2 with low or no expression of CX 3 CR1 across different species.…”
Section: Monocytes and Monocyte-derived Macrophagesmentioning
confidence: 99%
“…Others have suggested the acquisition of the repair M2 phenotype from M1 macrophages in sterile wounds. Early recruited peripheral monocytes/macrophages are predominantly Ly-6C hi (CCR2 + ) cells that become M1 tissue macrophages in the stroked hemisphere [25,80,114,115]. Once recruited, these Fig.…”
Section: Macrophage Polarization In Strokementioning
confidence: 99%
See 1 more Smart Citation